Temporary use & collective action - Robin A. Chang (PlaNext, 2018)
Amongst the proliferation of practice- and theory-based concepts that are changing urban planning, the renaissance of resilience is proving its potential for impressive implications instead of remaining a brief trend. This paper considers the affordances of an evolutionary and adaptive resilience framing for planning policy and practice in relation to economic development. Specifically, the research presented here explores the explanatory and analytical values of resilience through transformative collective action that incites experimentation, social learning and adaptive capacity building through entrepreneurial temporary uses. In the spotlight is Bremen’s temporary use policy of ZwischenZeitZentrale, through which temporary use is managed in the wake of economic and structural change. This softer form of policy demonstrates how planning mechanisms can complement strategies to address hurdles following gradual forms of crises. Through the case study of Plantage 9, an illustration of collective action is anchored by entrepreneurial temporary use that enable temporary users, temporary use managers and public administrations to build adaptive capacity for economic resilience.